2014
DOI: 10.1115/1.4026863
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow and Heat Transfer Characteristics of Microencapsulated Phase Change Material Slurry in Turbulent Flow

Abstract: Microencapsulated phase change material (MPCM) slurry is consisted of a base fluid in which MPCM is dispersed. Due to apparent high heat capacity associated with phase change process, MPCM slurry can be used as a viable heat transfer fluid (HTF) for turbulent flow conditions. Heat transfer and fluid flow properties of the slurry in turbulent flow (3000 < Re < 6000) were determined experimentally. Dynamic viscosity of the MPCM slurry was measured at different temperatures close to the melting point of the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The experimental results clearly showed that the viscosity of MPCM slurry is independent of shear rate and the coefficient of variation r X of the viscosity is less than 1.2%. Therefore, it can be concluded that MPCM slurries behaves as Newtonian fluids at the tested mass fractions, ranging from 2.1% to 10.9%, which is consistent with previous experiments and observations [1,3,8,9]. Using the temperature-dependent viscosity data, the Andrade equation was used for estimating fluid viscosity as a function of fluid temperature, which is defined as follows:…”
Section: Viscosity Measurement Of Mpcm Slurrysupporting
confidence: 54%
See 4 more Smart Citations
“…The experimental results clearly showed that the viscosity of MPCM slurry is independent of shear rate and the coefficient of variation r X of the viscosity is less than 1.2%. Therefore, it can be concluded that MPCM slurries behaves as Newtonian fluids at the tested mass fractions, ranging from 2.1% to 10.9%, which is consistent with previous experiments and observations [1,3,8,9]. Using the temperature-dependent viscosity data, the Andrade equation was used for estimating fluid viscosity as a function of fluid temperature, which is defined as follows:…”
Section: Viscosity Measurement Of Mpcm Slurrysupporting
confidence: 54%
“…They also found that the heat transfer coefficient was affected by the slurry velocity more significantly than by heat flux. Taherian et al [3] measured the heat transfer coefficient of MPCM slurry under turbulent flow conditions using a horizontal circular tube as well. The experimental results showed that the heat transfer coefficient decreased with increasing the mass fraction of MPCM in the slurry at the same fluid velocity because of the reduced momentum transfer between the fluid and the tube wall.…”
Section: Heat Transfer Of Mpcm Slurrymentioning
confidence: 99%
See 3 more Smart Citations